The Effect of Sales Growth and Fixed Asset Intensity On Tax Avoidance Moderated by Institutional Ownership - Stefanie Martchellia Suteja (PT. Publikasiku Academic Solution, 2023)
The purpose of the study is to obtain knowledge about the effect of sales growth and fixed asset intensity on tax avoidance and see the role of institutional ownership in strengthening or weakening the two independent variables on tax avoidance as the dependent variable in this study. The data used in this study is secondary data derived from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The method used in this study is a qualitative approach method, with samples in this study selected using the purposive sampling method. The results showed that institutional ownership was unable to weaken the effect of sales growth on tax avoidance, so the third hypothesis was rejected. In addition, institutional ownership is also unable to weaken the effect of fixed asset intensity on tax avoidance, so the fourth hypothesis is also rejected. Overall, the study concluded that sales growth did not have a significant effect on tax avoidance, while fixed asset intensity had a significant effect only on non-conforming tax. In addition, institutional ownership is unable to moderate the effect of sales growth and fixed asset intensity on tax avoidance. These findings provide an important understanding of the factors influencing tax avoidance practices in the context of sales growth, fixed asset intensity, and institutional ownership.